Incidental finding of a DMD exons 48–55 deletion during prenatal diagnosis - Zhang, Min; Lin, Zhaodong; Chen, Meihuan; Guo, Danhua; Yang, Qiaomei; He, Qianqian; Mao, Bin; Liang, Bin; Chen, Lingji; Cai, Meiying; Huang, Hailong; Xu, Liangpu (Frontiers in Pediatrics, 2025)
BackgroundDMD genetic variants cause a spectrum of phenotypes, from severe progressive proximal muscle weakness and degeneration leading to wheelchair dependence and death from cardiac and/or respiratory failure to very mild muscular phenotypes; very rarely, cases are completely asymptomatic. Few cases have been reported in males carrying DMD deletions who are asymptomatic.MethodsFamily clinical information was collected from the patients. A single nucleotide polymorphism array (SNP-array) was used to detect abnormalities in prenatal diagnosis, and multiplex ligation-dependent probe amplification (MLPA) and long-read sequencing (LRS) were used to confirm the detected variant.ResultsWe incidentally identified DMD exons 48–55 deletion using SNP-array in prenatal diagnosis; the variant was confirmed using MLPA and LRS, and the fragment size and precise locations of breakpoints were determined. The variant was precisely located at genomic position chrX:31640088–31945085, spanning from intron 47 to intron 56 in DMD. Serum biochemical indicators were normal in the male with the deletion.ConclusionOur study is the first to report a DMD exons 48–55 deletion in prenatal diagnosis. The phenotypes of DMD variants are diverse, and this study suggests that prediction of clinical severity based solely on molecular findings should be interpreted with caution.